Monetary Policy and Polish Labour Market in the years 1999–2008 - Grabia, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2010)
This article sets out to analyse how the monetary policy pursued by the National Bank of Poland (NBP) determined the labour market situation in the country in the decade 1999-2008. The article consists of introduction as well as five sections. Section one discusses NBP's strategy of monetary policy in the defined period against monetary strategies implemented in other countries. Section two uses the growth rates of money supply and of real GDP to verify whether the primary purpose of monetary policy, i.e. the inflationary target, was achieved. Section three generally characterises the country's labour market using the levels and dynamics of employment and of unemployment. Section four discusses major instruments of NBP's monetary policy, mainly analysing changes in the central bank's interest rates and their effect on the economic situation and on the labour market. The article concludes with a summation providing synthetic conclusions.